2016
DOI: 10.1007/978-3-319-43671-5_61
|View full text |Cite
|
Sign up to set email alerts
|

OpenADR—Intelligent Electrical Energy Consumption Towards Internet-of-Things

Abstract: With the growing of intermittent renewable energy sources, like wind and solar, are required energy backup solutions to establish an advantageous compromise between the energy production and consumption. Typically, these renewable energy sources are not installed at the end-users level, which can create the problem of uncontrolled distributed energy sources. In this research work we propose a solution based on the standard OpenADR to handle this problem, creating a platform based on internet-of-things capable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Besides all the improvements the system provided, both students and employees sense of comfort has increased. We use only open source software [29][30][31], where a set of pre-defined templates, that can be used to other cases, allows data visualization and from this consumption, reports are available in real-time. From another tested implementation at our university campus, we found that, at public places where local administrator entity does not enrol in sustainability actions, this proposed approach also works, but it doesn't provide increasing savings through time, because the system works partly based on initial performed configuration and also further user interactions to perfect the implemented rules from the gathered data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides all the improvements the system provided, both students and employees sense of comfort has increased. We use only open source software [29][30][31], where a set of pre-defined templates, that can be used to other cases, allows data visualization and from this consumption, reports are available in real-time. From another tested implementation at our university campus, we found that, at public places where local administrator entity does not enrol in sustainability actions, this proposed approach also works, but it doesn't provide increasing savings through time, because the system works partly based on initial performed configuration and also further user interactions to perfect the implemented rules from the gathered data.…”
Section: Discussionmentioning
confidence: 99%
“…Most important savings are achieved with the heating/cooling system working times, but we can also apply saving rules to lights and other electrical appliances. These working rules can be programmed to work automatic using infrared remote commands on air conditioners or even with the application of an openADR standard [9,31]. This protocol allows the remote turn on/off and any appliance that has this standard implemented.…”
Section: Energy Reducing Approachesmentioning
confidence: 99%
“…Also, Node-Red approaches (flow-based programming for the Internet of Things) available in most IoT platforms allow for the identification of actions based on the sensor data received. This is used to perform OpenADR on/off commands over a pre-defined appliance using data decision criteria [7]. This data comes from the appliance-associated smart meters and external data reception (like renewable energy production) [7].…”
Section: Iot Platformsmentioning
confidence: 99%
“…This service is charged based on the time that the predefined power is available. For example, a 1 MW generator kept "spinning" and ready during a 24 h period would be sold as 1 MW-day, even though no energy was actually produced [7]. Based on this fact, and taking into account that EVs remain plugged in during most of the daytime [8,9], consumption patterns may change from case to case, but it is possible to forecast patterns using historical data analysed using a data mining approach [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation